Some remarks on the Severi varieties of surfaces in ℙ3 - Xi Chen (International Journal of Mathematics and Mathematical Sciences)
Continuing the work of Chiantini and Ciliberto (1999) on the Severi varieties of curves on surfaces in ℙ3, we complete the proof of the existence of regular components for such varieties.